Trends and Patterns of Sediment Contamination in Indonesia (1999-2024): A Scientometric Analysis - Hanun, Alain Shofia; Budihardjo, Mochamad Arief; Andarani, Pertiwi; Fadhillah, Muhammad Afdhal (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
In the current era of the Industrial Revolution, there is a substantial increase in effluents from industrial discharges and domestic waste flowing into the sea, leading to contamination of water bodies. This includes pollutants such as heavy metals (Cu, Pb, and Zn) and microplastics, which eventually settle and contaminate sediments. Research on sediment contamination in Indonesia has been quite numerous and varied, but none has employed the scientometric method to analyze the trend of sediment contamination. Using CiteSpace, this study analyzes trends and patterns in research topics, citation frequency, and publication numbers over the past 25 years, based on co-occurrence, co-word, and co-citation analyses. The study examined 177 research articles indexed by Scopus. Findings reveal substantial international collaboration, with Indonesia leading with 167 publications, Malaysia with 19, and Japan with 15, showing a significant gap. The research spans various subject areas, including Environmental Science (111 articles), Earth and Planetary Sciences (74 articles), and Agricultural and Biological Sciences (55 articles). This study will provide a quantitative and visual overview of sediment contamination research in Indonesia, offering a comprehensive discussion of the findings.